LITERATUR SURVEY : PEMANFAATAN TEKNOLOGI UNTUK PENGELOLAAN SAMPAH - Ma'we, Hannatul; Fitriani Fitriani; Heri Wijayanto (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
The majority of countries are currently struggling with unsustainable levels of waste production and lack of recycling, especially household waste, and this field is in dire need of new solutions. In general, the waste management sector has difficulties with a lack of consumer trust, fraud, manipulation, significant manual processes, and low levels of information and control. Waste is the result of waste from various activities carried out daily by humans who do not have clothing, as a result of which waste can cause losses because it will cause floods, increase climate warming, cause bad odors, disturb beauty to worsen environmental sanitation. The purpose of this study is to provide an overview of various studies on Waste Management by utilizing technology, namely how methods are applied in regions in Indonesia and other countries in managing waste both waste from households, hazardous biomass, and industry. The study also reviewed 12 scientific papers that have been published in various international journals. The most frequently used management method is utilizing technology based on websites, android, and blockchain with waterfall and incremental software development processes. Keywords: Enter keywords or phrases in alphabetical order, separated by commas. The number of keywords must be between 3-5 words.